The Impact of English Morphological Awareness on Vocabulary Enrichment: A Causal-Affect Relationship Research - Wardana, I Ketut (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
Limited vocabulary is one of the most common difficulties faced by EFL learners in Indonesia. Ignorance of English morphological awareness prevents students from expanding lexical words. However, research on morphological consciousness is relatively rare. Therefore, this study aims to examine the impact of morphological awareness on EFL learners’ vocabulary. The study used a causal-effect relationship research design. The population consisted exclusively of students of the English and Management Studies program at Universitas Mahasaraswati Denpasar (N=1360). However, in this study, only 10% of the population (N = 136) was sampled using a systematic random sampling technique. There were two types of instruments: Instrument A was ten successful two-layer multiple-choice morphology tests and Instrument B was vocabulary completion tests. The data were then analyzed using statistical mediation regression and a series of independent-sample t-tests. The results indicated that the participants' perception of the derivation morphology was rated as